The Anthropology of Hunter-Gatherers : Key Themes for Archaeologists - Cummings, Vicki (Debates in Archaeology Ser, 2013)
Cover -- Title -- Series -- Dedication -- Contents -- List of figures -- List of tables -- Preface -- A note on names -- Acknowledgements -- 1 Introduction: Can the study of modern hunter-gatherers help us understand the past? -- The aim of the volume -- What constitutes a 'modern' hunter-gatherer and who studies them? -- What is ethnographic analogy? -- Analogy -- Conclusion -- 2 Making a living: Hunter-gatherer subsistence -- Introduction -- Hunting -- Gathering -- Fishing and marine resources -- Immediate and delayed return systems -- Beyond hunting and gathering: Dealing with domestication and domesticates -- Ethnographic analogy: Understanding past subsistence -- Conclusions -- 3 Moving on up: Mobility and settlement -- Introduction -- Why do hunter-gatherers move? -- Hunter-gatherer sites and dwellings -- Hunter-gatherer sedentism -- Problems of ethnographic analogy -- Conclusions -- 4 Complex issues: Society and social organization -- Introduction -- Characterizing society -- Hunter-gatherers and gender -- Kinship -- Problems of ethnographic analogy -- Conclusions -- 5 Thinking about the world: Hunter-gatherer belief systems -- Introduction -- Animism -- Creation mythology and understanding the universe -- Shamanism? -- Rites of passage: From birth to death -- The use of ethnographic analogy -- Conclusions -- 6 Being in the world: Hunter-gatherer landscapes -- Introduction -- Landscapes and hunter-gatherers -- The moral landscape -- Hunter-gatherer rock art -- The use of ethnographic analogy -- Conclusions -- 7 Living in a material world: Hunter-gatherer material culture -- Introduction -- Hunter-gatherer material culture -- Sharing, trade, exchange and gift-giving -- Problems of ethnographic analogy -- Conclusion -- 8 Conclusions: How the study of modern hunter-gatherers can help us understand the pastt -- Introduction.